IMPLEMENTASI ELEKTRONIFIKASI PEMBAYARAN DI LEMBAGA TMI AL-AMIEN PRENDUAN SUMENEP MADURA - Sudianto, Anisatur Rahmah, Supandi (Universitas Islam Madura, 2021)
Moving forward following technological developments, some Islamic boarding schools have succeeded in changing the paradigm of society that regards pondok pesantren as orthodox, ancient and far from modern. Exploring an era that has penetrated into an all-digital era, many pesantren have been interested in using payment electronification. This study aims to determine the practice of payment electronification at the TMI Al-Amien Prenduan institution and to identify obstacles and efforts in implementing payment electronification at theinstitution Tarbiyatul Mu'allimien Al-Islamiyah. By using a qualitative approach, this research uses data collection methods by conducting interviews, and documentation. From study this, the researchers concluded that the Al-Amien Prenduan pesantren, the TMI institution, can implement payment electronification at the pesantren and with this technology helps the activity of the pesantren become orderly and more efficient in managing finances.